Analisis Gangguan Transmisi Fiber Cut dan Pengembangan Solusi untuk Meningkatkan Availability Sistem Komunikasi Fiber Optik Section Banua Hanyar – Bati Bati - Muhammad Gani Baihaqi Darussalam; Ahmad Fauzi; Muhammad Galura Suranegara; Dwi Wahyu Lestariningsih (Dinasti Research, 2024)
Technology continues to develop very quickly, especially long-distance communication and transmission technology. This is due to the increasing human need for the internet, as seen by its availability. The main objective of this research is to analyze the impact and solution to Fiber Cut transmission on availability in the Banua Hanyar - Bati Bati Section. This research uses a correlative descriptive quantitative method to obtain a solution, namely replacing ordinary fiber optic cables and many existing cable with a new anti-rodent fiber optic cable 3 km long located 0.8 km to 3.8 km from Banua Hanyar. This solution is said to be very influential because it succeeded in increasing the availability of the Banua Hanyar - Bati Bati Section system to 100%.